2010
DOI: 10.1007/s10750-010-0393-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet patterns and ontogenetic diet shift of pikeperch, Sander lucioperca (L.) fry in lakes Peipsi and Võrtsjärv (Estonia)

Abstract: Pikeperch is a major predator in the pelagic zone of eutrophic waters, such as the large north-temperate lowland lakes Võrtsjärv (Estonia) and Peipsi (Estonia/Russia). The size and structure of the pikeperch population is strongly influenced by their success at the juvenile stage. Therefore, we investigated the diet and prey selection of pikeperch fry caught in the ice-free period in lakes Peipsi and Võrtsjärv in 2007 and 2008. We analysed the stomach contents of 635 pikeperch from Lake Peipsi and 202 pikeperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Scarce occurrence of adult copepods (particularly large egg-carrying females) indicates the pressure of fish. In a recent study (Ginter et al, 2011) on the stomach content of pikeperch fry, the Ivlev selectivity index revealed high positive selection for adult M. leuckarti. The calanoid copepod E. gracilis is a species of lower trophy (Chapman, 1969;Gulati, 1984;Shumka, 2001;May and O'Hare, 2005;Vǣrvågen and Nilssen, 2010) and was numerous in the 1950s (Shönberg, 1958) and even in the 1960s.…”
Section: Tabmentioning
confidence: 97%
“…Scarce occurrence of adult copepods (particularly large egg-carrying females) indicates the pressure of fish. In a recent study (Ginter et al, 2011) on the stomach content of pikeperch fry, the Ivlev selectivity index revealed high positive selection for adult M. leuckarti. The calanoid copepod E. gracilis is a species of lower trophy (Chapman, 1969;Gulati, 1984;Shumka, 2001;May and O'Hare, 2005;Vǣrvågen and Nilssen, 2010) and was numerous in the 1950s (Shönberg, 1958) and even in the 1960s.…”
Section: Tabmentioning
confidence: 97%
“…Our previous investigations (Ginter et al, 2011(Ginter et al, , 2012a have shown that mismatches in predator and prey sizes have triggered a postponement of the shift to a piscivory diet among the pikeperch in Lakes Peipsi and Võrtsjärv. However, recently, winters have become milder, and juvenile pikeperch are now capable of surviving the first winter at smaller sizes and without shifting to a piscivory diet in these Estonian lakes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prey-predator length relationship decreased towards autumn and pikeperch was able to shift to piscivory in spring, being 7.6 -8.5 cm in length [13]. In 2007 and 2008 the average autumn length (± standard deviation) of pikeperch fry was 6.2 ± 0.8 cm and 6.1 ± 0.9 cm, respectively [17]. In 2009 and 2010 it was 5.5 ± 1.1 cm and 5.6 ± 0.8 cm, respectively ( Table 3 In the recent period, the first fishes eaten by pikeperch were ruffe and pikeperch.…”
Section: Growth and The Ontogenetic Diet Shiftmentioning
confidence: 99%
“…The diet and growth of juvenile pikeperch have been studied several times since 1920 in a large shallow Lake Võrtsjärv [12][13][14][15][16][17]. Moreover, the probability of major shifts in the feeding modes of fish is especially high in shallow lakes [11] such as Lake Võrtsjärv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation